Access to Social Security for the Rural Elderly in Vietnam - Tran Quy Long (Wieś i Rolnictwo)
The current situation of the socio-economic life of the elderly now in part reflects Vietnam’s historical characteristics. The socio-economic structure in Vietnam has changed drastically due to the development of market relations, migration, the transformation of traditional society and modern agricultural societies that are creating forms and levels of socio-economic risk for the elderly. Based on the data from two communes, the article shows that, older men are more likely to receive monthly social transfers than women. Elder ly people with higher education receive higher monthly social benefits than lower education one. The elderly in rural areas surveyed hardly enjoy any social welfare programmes. The only beneficiaries are those who must be 80 years or older without a pension or other allowance. Some older people are entitled to benefits but only from programmes not reserved for the elderly. In order to live, the elderly still have to work, mainly in agriculture. This fact reflects the contrast and inadequacy of retirement and health regulations, which stipulate that workers must stop working at a certain age. The enjoyment of social welfare differs between elderly groups with different personal and social characteristics. It can be said that elderly people in rural areas who are not entitled to social welfare benefits are “double disadvantaged”. This mandates that the policy should be aimed at all the elderly in ensuring social welfare. Along with this, it is necessary to have a roadmap to increase the level of monthly social welfare benefits for the elderly to gradually achieve the minimum living standard because the current level of support for the elderly in Vietnam is still much lower than the comparable level for the poor. The process of population ageing in Vietnam is bringing great opportunities as well as great challenges, requiring new approaches to pensions, social pensions, health and the social environment for the elderly in rural areas.